Assessing posture while playing in musicians – A systematic review. (January 2023) - Rousseau, Céleste; Taha, Louna; Barton, Gabor; Garden, Peter; Baltzopoulos, Vasilios
Abstract: Introduction: Playing a musical instrument can potentially lead to musculoskeletal disorders. Postural loads are different considering the instrument they play; for example violin and flute require elevation from both upper limbs, asymmetrical postures are common and instrument weight can be significant. The aim was to explore how musicians' postures are investigated, and potentially if there is evidence of an association between postural impairments and pain. Methods: A systematic search was performed in several databases, combined with manual search. Study inclusion, data extraction and quality assessment were performed independently by two reviewers. Results: Twenty seven relevant studies were included in this review covering musicians with the full range of playing experience (professionals, students, teachers, amateurs). The main considered methods to investigate postures are visual assessment and three dimensional analysis using videography. Discussion: This review provides a synthesis of the different methods used to monitor posture in musicians and provides information in order to build protocols which will allow comparison with previous work. Highlights: Visual assessment and three-dimensional analysis are the most reported ways to investigate posture while playing. Considered "physiological" posture is not often thoroughly or specifically described in the different papers. There is no strong evidence to assume that postural impairments while playing and pain in musicians are associated.